A novel positive selection system for plant transformation based on microbial biuret hydrolase and biuret - Xiaowei Luo; Qiuyan Yu; Di Hu; Ming Gong; Zhurong Zou (PLoS ONE, 2026)
Conventional selectable marker genes (SMGs) in plant transformation, such as those conferring antibiotic resistance, raise biosafety concerns due to their permanent genomic integration. Alternative systems, such as the phosphite (Phi)/phosphite dehydrogenase (PtxD) system, have been developed to address these concerns. This system works by enabling transgenic plants to convert non-metabolizable, toxic Phi into usable orthophosphate (Pi), thereby providing both a detoxification mechanism and a positive growth advantage for selection. Building on this principle of detoxification-based positive selection, we have developed a novel system utilizing the microbial biuret hydrolase (BH) gene and its substrate, biuret (BU). Biuret is a phytotoxic by-product found in urea fertilizers. We introduced two genetic constructs into tobacco via Agrobacterium-mediated transformation: one expressing only the BH enzyme and another expressing a dual-function BH–AH fusion protein (BA2H, where AH is allophanate hydrolase). On nitrate-containing media, selection with 1 mM BU achieved a transformation efficiency of nearly 80% and shortened regeneration time by approximately 20 days compared to conventional Kanamycin selection (66.7% efficiency). The resulting transgenic lines demonstrated strong tolerance to BU during germination and seedling growth, even under nitrogen-deficient conditions. BU also acted as a selective herbicide, reducing weed biomass by ~70% in co-culture and field-simulation experiments while transgenic plants thrived. The BH/BU system provides an efficient, safe, and agriculturally relevant selection platform that avoids antibiotic resistance markers and leverages BU’s dual role as a nitrogen source for crops and a growth inhibitor for weeds. This approach offers a sustainable alternative to conventional selection markers in plant biotechnology.